Saberes de uma prisão incomum: o processo de trabalho de formadores em uma unidade da Associação de Proteção e Assistência aos Condenados - APAC - Renan Luiz Senra Barbosa (2021)
This research analyzes the working process of trainers in a unit of the Association for Protection and Assistance to Convicts (APAC), a system which is referred as contradictory since it is a reference for community management of an unusual prison unit, comparing to conventional prison system managed by the State. Analyzing concepts, guidelines and methods employed for the orientation and practice of educational actors, whom we call trainers, the aim is to identify their contributions to integral education through investigations approaching educational practices in prisons. The proposed methodology is a qualitative research with a case study approach and field observation, conducting interviews through a questionnaire and focus groups as research instruments. The theoretical framework includes authors such as Paulo Freire, as well as more recent authors, besides the study based on the legislation on Criminal Execution Law and Youth and Adult Education in Brazil, applied in schools and in other settings. The purpose is to understand how teaching practices may interact with emancipatory education in this specific context. Considering the coronavirus pandemic, however an adaptation was done in the methodology proposed in order to carry out remote interviews and meetings. The research has made it possible to understand how trainers working in an unusual prison unit may enhance the benefits of youth and adult education in school environment.